Severe quadriparesis caused by wasp sting - Bánovcin, Peter; Havlíceková, Zuzana; Jesenák, Milos; Nosál, Slavomír; Durdík, Peter; Ciljaková, Miriam; Mikler, Ján (The Turkish Journal of Pediatrics, 2009)
Besides the typical symptoms of allergic reaction after wasp sting, unusual and unexpected reactions may also develop. In this report, a case of severe peripheral quadriparesis and sphincteric disorder (urinary incontinence) in a 10-year-old boy occurring within 24 hours after wasp sting is presented. Corticosteroids had very good therapeutic effect, and improvement in clinical status was observed within 72 hours. The exact pathogenic mechanism of peripheral nervous system damage is not very well known. Several studies have suggested that besides the neurotoxic effect of wasp venom, delayed immunological response to wasp antigens followed by an allergy-triggered autoimmune reaction is possible. Wasp venom may activate an allergic reaction or effects by toxic impacts; however, typical clinical symptoms of allergic reaction are not necessarily present.